Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

hreeg97

  • 3 years ago

2x-y+z=-4 3x+y-2z=0 3x-y=-4 i have to solve it using elimination and i am so lost!

  • This Question is Closed
  1. vitorfleite
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    2x-y+z=-4 (*2) 3x+y-2z=0 (the same) 3x-y=-4 (*-)

  2. vitorfleite
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    So, 4x-2y+2z=-8 3x+y-2z=0 -3x+y=4

  3. vitorfleite
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Answer: x=-1 y=1 z=-1

  4. hreeg97
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    thanks so much

  5. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy